THE INFLUENCE OF SELF-EFFICACY AND MOTIVATION TO TEACHER MOTIVATION WITH THE MEDIATION OF ORGANIZATIONAL COMMITMENT A CASE STUDY ON SMP NEGERI IN BATANGAN SUB DISTRICT, PATI REGENCY (PUBLIC JUNIOR HIGH SCHOOLS) - Pujiati, 12.52.02.0032; Liana, Lie (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study is intended to analyze the effect of self efficacy and motivatoin to Teacher performance with mediationorganizational commitment. Population is used as the object of the teachers in SMP Pati totaling 84 people. Sampling was purposive sampling methods that sample selected according to criteria that are determined to be the respondent. Of p0pulasition sensus results can be seen that the number of samples in this study were 84 respondents. The results prove that the models ability to correctly describe the effect of variable Self-efficacy and Organizational Commitment to Motivation is 54.4%. While others described by 45.6% to a variable outside the regression model. self efficacy and effects, motivation, organizational commitment to teacher performance by 69.5%. While the other 30.5% is explained beyond this regression model. Self-efficacy with mediation organizational commitment does not have a significant impact on teacher performance in SMPBatangan. Mediation test results note that the value is greater than the direct effect of the indirect effect. Motivation with organizational commitment mediation proved to have a significant impact on teacher performance in SMP NBatangan. The test results prove the direct influence of greater value than the value of the indirect effect. Keywords: Teacher Self-efficacy, Motivation, Organizational Commitment, Teacher Performance